Аналіз ефективності технологій розроблення мобільних застосунків для OC ANDROID - Федорченко, В. М.; Поляков, А. О.; Сєвєрінов, О. В.; Fedorchenko, V. M.; Poliakov, A.; Sievierinov, O. (Харківський національний автомобільно-дорожній університет; Північно-Східний науковий центр транспортної академії України, 2022)
Запропонована стаття резюмує результати проведеного авторами дослідження щодо вибору платформ розроблення мобільних додатків для ОС Android з урахуванням їхньої продуктивності. Пропонується метод аналізу продуктивності на основі профілювання додатку за пам’яттю, за завантаженням процесора, за кількістю коду та мережної активності. За результатами дослідження платформа Xamarin має обмеження з боку дозволів, потребує більше ресурсів як пам’яті, так енергії живлення, що може бути відчутним у великих застосунках.

Problem.Mobile application development is quite a complex process that requires developers with high expertise in a particular development plat-form for Android.There are also several single-platform,cross-platform,Xamarin development plat-forms but there is no comparison of their perfor-mance as with nativeones.Methodology.As a meth-od, it is proposed to use an experimental approach in which a mobile application is developed with thenecessary components, and thenthe performance of the profiler on the metrics of CPU usage, memory, power consumption and networkis investigated.Results. According to the study, the Xamarin plat-form has additional restrictions on permissions, requires more resources, both memory and power, which can be felt in large applications, but allows you to attract a large community of .Net developers.
Analyzingthe efficiency of technologies for developing mobile applicationsfor Android OS
Keywords: ОС Android; мобільна платформа; native-платформа; мультиплатформна розробка; кросплатформеність; Android profiler; платформа Xamarin; Android OS; mobile platform; native platform; multi-platform development; cross-platform; Android profiler; Xamarin platform